2020
DOI: 10.1002/14651858.cd012991.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuroprosthesis for promoting recovery of function after stroke

Abstract: BackgroundMotor neuroprosthesis (MN) involves electrical stimulation of neural structures by miniaturized devices to allow the performance of tasks in the natural environment in which people live (home and community context), as an orthosis. In this way, daily use of these devices could act as an environmental facilitator for increasing the activities and participation of people with stroke. ObjectivesTo assess the e ects of MN for improving independence in activities of daily living (ADL), activities involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 141 publications
0
7
0
Order By: Relevance
“…The research reported 19 systematic reviews [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Almost all the reviews dealt with aspects of effectiveness and/or acceptance in some way, and several also dealt with multiple issues at the same time.…”
Section: The Outcome Of the Narrative Review Based On The Umbrella Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…The research reported 19 systematic reviews [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Almost all the reviews dealt with aspects of effectiveness and/or acceptance in some way, and several also dealt with multiple issues at the same time.…”
Section: The Outcome Of the Narrative Review Based On The Umbrella Re...mentioning
confidence: 99%
“…Two studies [46,50] specifically addressed the empowerment of people with motor disabilities using assistive technology solutions. However, the studies reported in Section 3.3.1 [43,48,57] also touched on this field, although to a lesser extent and from a different angle.…”
Section: Empowering Motor Disabilities Through Assistive Technology S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The first consideration drawn from this review is that using smart robotic devices in the rehabilitation process is an emerging field that requires more effort and focus. The fact that Cochrane Library has multiple recent systematic reviews that include clinical trials of RAT for stroke patients, proves the importance of the field [55]- [57]. Despite of the great attention drawn to RAT for sensorimotor defects, the majority of robotic devices were designed for adult patients recovering from chronic stroke [58].…”
Section: Challenges and Future Studiesmentioning
confidence: 99%
“…Previous consensus on contraindications and precautions associated with using PAMs from various organisations was released in the early 2000s 6–8. Still, they have become outdated in light of technological advancements of the last years 9 10. A recent scoping review of the literature5 examined several systematic reviews on the safety of commonly used PAMs.…”
Section: Introductionmentioning
confidence: 99%